Optimal Homotopy Analysis Method for Solving Fractional Klein-Gordon Equations - Alkan, Aslı (Ankara Üniversitesi, 2026)
In the study, the new numerical solutions of fractional Klein-Gordon equations are obtained by utilizing the optimal homotopy analysis method. We determine the residual error function for the selection of arbitrary parameter $\hbar$. The serial solutions of fractional Klein-Gordon equations have been obtained satisfactorily by applying this technique. Based on the solutions derived from the requisite equations, it has been demonstrated that this method is applicable to fractional partial differential equations.
Keywords: Numerical Analysis; Sayısal Analiz